A new seco-clerodane-type diterpenoid from Bornean liverwort Schistochila acuminate - Ng, Shean Yeaw; Takashi Kamada; Monica Suleiman; Charles Santhanaraju Vairappan (Natural Product Incorporation, 2016)
A new compound, schistochilic acid D (1) and two known compounds (2 and 3) were isolated from MeOH extract of Bornean liverwort Schistochila acuminata collected from Mount Trus Madi, Sabah. The structure of the new metabolite was established based on spectroscopic (1D NMR, 2D NMR, and IR). And HRESIMS data. In addition, another population of S. Acuminata collected from Mount Alab (Sabah) yielded four known compounds, 2, 3, 4 and 5. These compounds were tested for their biological potential against the B16-F10 cell line. Compounds 4 and 5 exhibited weak cytotoxic activity.